Diseño y producción de un desinfectante para frutas y verduras a base de suero de leche. - Guevara Lascano, Sergio Xavier (2020)
Whey is a by-product obtained from the precipitation of casein in the manufacture of cheese, retaining 50 % of the solids of milk such as protein, minerals, lactose and vitamin. In the past it was considered as waste in the cheese factories but nowadays thanks to the research it is known that it is a rich source of nutritional elements so in a way it is used to feed pigs and in functional foods for people as protein powder. The main objective of this project is to characterize the processes of this by-product and its proteins in the design and elaboration of a disinfection of fruits and vegetables, also in a certain way to contribute to what are good manufacturing practices if we see it from the agricultural industry as far as production of fruits and vegetables is concerned, since everything that it takes to grow a product from the ground deals with what are pesticides, It is not known whether the vegetables are contaminated with bacteria or viruses when they are harvested, although it is known that a jet of water when rinsed would eliminate several fungicides, but it is even more certain that it would not completely eliminate viruses or bacteria to which the products have been exposed through handling from producers to consumers.